2017
DOI: 10.21037/jtd.2017.03.122
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblasts: more than mechanical support

Abstract: Fibroblasts are cells with a structural function, synthesizing components of the extracellular matrix. They are accordingly associated with various forms of connective tissue. During cardiac development fibroblasts originate from different sources. Most derive from the epicardium, some derive from the endocardium, and a small population derives from the neural crest. Cardiac fibroblasts have important functions during development, homeostasis, and disease. However, since fibroblasts are a very heterogeneous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 66 publications
(179 reference statements)
2
64
0
Order By: Relevance
“…The expression of ECM genes increased during CM and cardiac fibroblast maturation ( Figures 2C-2F and 3), sharply increasing from 5W to 6W. ECM proteins were previously considered to be derived primarily from fibroblasts and to provide only physical support for the cells; however, a growing body of evidence indicates that ECM proteins may be generated from CMs or other cell types as well, and these proteins have a wide variety of effects on cellular processes, including cell proliferation, differentiation, and migration, especially during embryogenesis (Doppler et al, 2017;Lockhart et al, 2011). Therefore, the synergistic increase in a large number of ECM proteins may contribute to CM differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of ECM genes increased during CM and cardiac fibroblast maturation ( Figures 2C-2F and 3), sharply increasing from 5W to 6W. ECM proteins were previously considered to be derived primarily from fibroblasts and to provide only physical support for the cells; however, a growing body of evidence indicates that ECM proteins may be generated from CMs or other cell types as well, and these proteins have a wide variety of effects on cellular processes, including cell proliferation, differentiation, and migration, especially during embryogenesis (Doppler et al, 2017;Lockhart et al, 2011). Therefore, the synergistic increase in a large number of ECM proteins may contribute to CM differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of mitosis-related genes, such as AURKB, CDK1, and UBE2C, were also decreased ( Figure S4F). The ECM plays a vital role in embryonic heart development because it provides structural support for cardiac cells, cellcell signaling, and cell migration and contributes to the regulation of cell proliferation and differentiation (Doppler et al, 2017). In fibroblasts, relative expression levels of ECM genes also gradually increased with heart development (Figures 4E and 4F).…”
Section: Developmental Pattern Of Cardiac Fibroblastsmentioning
confidence: 99%
“…Most cardiac fibroblasts in embryonic development arise from the PEO 57,65,66 , highlighting the necessity of proepicardial induction in developmental heart models. Immunofluorescence analysis of our hHOs revealed the presence of cardiac fibroblast markers including the membrane glycoprotein Thy1, which is involved in cell-cell and cell-matrix adhesion 66,67 , and the intermediate filament protein Vimentin, typically seen in cells of mesenchymal lineage 67 . Other cardiac fibroblast markers were found in the hHOs via RNA-sequencing analysis, including DDR2 66 which plays an important role in EMT and the FHF marker PDGFRα which is crucial for vascularization during development and is also a strong marker of cardiac fibroblasts 67 .…”
Section: Discussionmentioning
confidence: 95%
“…Because cardiac fibroblasts represent a heterogenous population with no specific cell markers, they are among the least characterised cell types relevant to heart health [37]. Although adult CFs promote cardiomyocyte hypertrophy, it has been shown that embryonic CFs contribute to proliferation of CMs through paracrine signalling [38].…”
Section: Cardiac Fibroblasts and Resident Immune Cellsmentioning
confidence: 99%